Pengujian Aktivitas Antioksidan Ekstrak Daun Ulin (Eusideroxylon zwageri) dengan Menggunakan Metode DPPH - Farida Aryani (Jurusan Teknologi Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2021)
Antioxidants are electron-donating compounds or reductants, these compounds have small molecular weights, but can deactivate the development of oxidation reactions by preventing the formation of free radicals. One of the plants that have potential as natural antioxidants is the Ulin leaf (Eusideroxylon zwageri). This study aims to determine the antioxidant activity of the extracts of young and old leaves of Ulin plants against DPPH radicals (1, 1-diphenyl-1-picrylhydrazyl) using a UV-Vis Spectrophotometer. Both young and old leaves were extracted using methanol at room temperature then concentrated using a vacuum rotary evaporator to obtain a crude extract. Phytochemical analysis was conducted to identify the secondary metabolite compounds which include flavonoids, alkaloids, tannins, terpenoid saponins, and steroids. To determine the antioxidant activity, the test was carried out with series concentrations aimed at calculating the IC50 value, the concentration at which the test sample was able to inhibit 50% of the free radical DPPH The phytochemical analysis showed that young and old leaves contained the same phytochemical content, specifically Flavonoids, Tannins, Saponins, terpenoids, while Alkaloids and steroids were not detected. The antioxidant activity test showed that the IC50 value of young leaves, old leaves, and Ascorbic acid as the positive control were 22.93 ppm, 13.31 ppm, and 7.08 ppm consecutively. This result shows that Ulin leaves are in a strong category because both young and old leaves have an IC50 value of less than 100 ppm.